2018
DOI: 10.1016/j.jpba.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Current possibilities of liquid chromatography for the characterization of antibody-drug conjugates

Abstract: Antibody Drug Conjugates (ADCs) are innovative biopharmaceuticals gaining increasing attention over the last two decades. The concept of ADCs lead to new therapy approaches in numerous oncological indications as well in infectious diseases. Currently, around 60 CECs are in clinical trials indicating the expanding importance of this class of protein therapeutics. ADCs show unprecedented intrinsic heterogeneity and address new quality attributes which have to be assessed. Liquid chromatography is one of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 95 publications
1
43
0
4
Order By: Relevance
“…The characterization of ADCs and their payloads using comprehensive LC modes has been described in an excellent review by Bobaly et al. .…”
Section: Native Lc Modesmentioning
confidence: 99%
“…The characterization of ADCs and their payloads using comprehensive LC modes has been described in an excellent review by Bobaly et al. .…”
Section: Native Lc Modesmentioning
confidence: 99%
“…As such, DAR values are considered critical quality attributes of ADCs, necessitating the development of a range of analytical methods for their quantitative evaluation. For example, many separation techniques have been utilized to accurately derive DAR values, such as hydrophobic interaction chromatography (HIC), ion exchange chromatography (IEC), reverse phase liquid chromatography (RPLC), capillary electrophoresis (CE), or capillary isoelectric focusing (cIEF) . As lysine‐conjugated ADCs typically exhibit greater heterogeneity and poorer chromatographic peak shapes than equivalent cysteine‐modified therapeutics, mass spectrometry (MS) is typically deployed for their DAR assessment .…”
Section: Introductionmentioning
confidence: 99%
“…When applying the novel protein A method on the model ADC, strong tailing was observed, which increased with the DAR. This suggests that this phenomenon is caused by a non‐specific interaction by the payload with the stationary phase . MAb 2,on the other hand, showed a much stronger interaction with the protein A caused by the second binding site at the Fab fragment, which only eluted after the gradient reached 100% buffer B.…”
Section: Discussionmentioning
confidence: 99%
“…This calls for more sophisticated analytical techniques and results in extensive method development for every individual ADC. It has been reported that the payload of ADCs can have an impact on the elution profile and resolution and can cause poor recoveries . Commonly used organic modifiers such as IPA, DMSO, propylene glycol or ACN can be applied to reduce non‐specific interaction of the payload with the stationary phase.…”
Section: Discussionmentioning
confidence: 99%